2011
DOI: 10.1177/0022219410391187
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Three Interventions on the Reading Skills of Children With Reading Disabilities in Grade 2

Abstract: In a longitudinal intervention study, the effects of three intervention strategies on the reading skills of children with reading disabilities in Grade 2 were analyzed. The interventions consisted of computerized training programs: One bottom-up intervention aimed at improving word decoding skills and phonological abilities, the second intervention focused on top-down processing on the word and sentence levels, and the third was a combination of these two training programs (n = 25 in each group). In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
1
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 37 publications
6
28
1
9
Order By: Relevance
“…The two factors in the SVR -decoding and language comprehension -explained somewhat less of the variance in reading ability in children with reading difficulties than in children with typical reading ability, suggesting that a more complex theory may be needed to explain reading for children with reading difficulties than the original SVR proposed by Gough and Tunmer (1986). This is also in line with findings that children with more general reading difficulties benefit from broad interventions combining several different bottom-up processes, as well as top-down processes (Gustafson et al, 2011).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The two factors in the SVR -decoding and language comprehension -explained somewhat less of the variance in reading ability in children with reading difficulties than in children with typical reading ability, suggesting that a more complex theory may be needed to explain reading for children with reading difficulties than the original SVR proposed by Gough and Tunmer (1986). This is also in line with findings that children with more general reading difficulties benefit from broad interventions combining several different bottom-up processes, as well as top-down processes (Gustafson et al, 2011).…”
Section: Discussionsupporting
confidence: 74%
“…As it was not possible to complete all test items there was no maximum score -the score was the number of correct answers minus the number of errors. In a previous study, testretest correlation between two test-sessions in grade 2 was r ¼ .91 (Gustafson et al, 2011).…”
Section: Methodsmentioning
confidence: 84%
See 1 more Smart Citation
“…This learning environment supports the child's access to long-term representations, shortterm maintenance and manipulation, sustained attention and engagement in working with the material, and is thus likely to facilitate learning (Mayer, 2008). In fact, Omega-is and its predecessors were developed with difficult learning situations in mind, and the program and its forerunners have shown positive effects on both word reading and reading comprehension in typically developing as well as children with, e.g., dyslexia, autism, and attention deficit hyperactivity disorder (e.g., Fälth, Gustafson, Tjus, Heimann, & Svensson, 2013;Gustafson, Fälth, Svensson, Tjus, & Heimann, 2011;Heimann, Nelson, Gillberg, & Karnevik, 1993;Heimann, Nelson, Tjus, & Gillberg, 1995;Helland, Tjus, Hovden, Ofte, & Heimann, 2011;Tjus, Heimann, & Nelson, 1998. Early versions of the program also indicated positive effects on reading development in deaf children (Prinz, Nelson, & Stedt, 1982;Prinz & Nelson, 1985).…”
Section: Using Interventions To Support Reading Developmentmentioning
confidence: 99%
“…In other words, word identification is likely to be a cause and not a consequence of reading comprehension difficulties. Studies have established that children who are experiencing reading difficulties have their core deficits in phonological skills (Gustafson, Falth, Svensson, Tjus, & Heimann, 2011;Fuchs et al, 2012;McNamara et al 2011, SasKatchewan, 2004. Fuchs et al (2012), for instance, found that phonological processing and Rapid Automatized Naming (RAN) were statistically significant predictors; they are important for explaining reading comprehension as well as reading at the word level.…”
Section: Relation Of Word Identification To Comprehension Of Textmentioning
confidence: 99%